The Effect of Meaningful Instructional Design (MID) Learning Model on Students' Mathematical Reasoning Ability on the Material of Arithmetic Rows and Rows in Class VIII SMP Negeri 2 Tebing Tinggi - Glean, Gohanna Rizky; Sidabutar, Ropinus; Simarmata , Gayus (EduMatika: Jurnal MIPA, 2023)
The aim of this research is to find out how the Meaningfull Instructional Design Learning Model influences students' Mathematical Reasoning abilities on the subject of number patterns, after implementing the Meaningfull Instructional Design (MID) Learning Model. The type of research used is the Pre-experimental Design research method. The research subjects were class VIII-9, totaling 30 people. In this research the author used a quantitative approach. The design used in this research is one-shot case study. Data collection techniques in this research are in the form of tests and questionnaires to determine students' mathematical reasoning abilities in the research process carried out. Data analysis techniques were carried out using normality, linearity and hypothesis testing. From the results of data analysis, it was obtained that the results of students' mathematical reasoning abilities showed that the influence was shown through the regression equation Y = 7.280 + 0.224X. This influence is through the t-test, namely ????count ????table(3.448 > 2.048) or p (sig.) < 0.05 (0.000 < 0.05), then H0 is rejected and H1 is accepted, which means there is an influence of the Meaningful Instructional Design Learning Model. It can be concluded that by applying the influence of the Meaningful Instructional Design Learning Model, it can improve students' mathematical reasoning abilities in students' mathematics learning material on number patterns in class VIII SMP Negeri 2 Tebing Tinggi for the 2023/2024 academic year.